Subsidized Home Ownership Credit Agreement at the Mataram Branch of PT. Bank Tabungan Negara - Sudiarto Sudiarto; Adhitya Bagus Singandaru; Adhitya Bayu Suryantara (Unram Law Review, 2022)
Regarding to the fulfillment of the housing needs of the society, Indonesian government finally issued a policy related to subsidized housing ownership for low-income groups by installments through banks. However, the fact provision of subsidized housing loans experienced bad credit due to a lack of prudence by the bank in analysis before granting credit. The research method used in this study is a normative research method, by using library materials as primary data, especially from literature. The results of this study are to avoid the possibility of bad credit in the provision of subsidized housing loans, the bank as the creditor must be able to apply the prudential principle by conducting credit analysis in approving a credit application submitted. The principle of bank prudence takes the form of the 5C principles, which then known as Character, Capacity, Capital, Collateral, Condition of economy.